2023
DOI: 10.1002/mgg3.2277
|View full text |Cite
|
Sign up to set email alerts
|

Familial gigantiform cementoma with recurrent ANO5 p.Cys356Tyr mutations: Clinicopathological and genetic study with literature review

Zheng Zhou,
Ye Zhang,
Lijing Zhu
et al.

Abstract: BackgroundFamilial gigantiform cementoma (FGC) is a rare tumor characterized by the early onset of multi‐quadrant fibro‐osseous lesions in the jaws, causing severe maxillofacial deformities. Its clinicopathological features overlap with those of other benign fibro‐osseous lesions. FGC eventually exhibits progressively rapid growth, but no suspected causative gene has been identified.MethodsIn this study, three patients with FGC were recruited, and genomic DNA from the tumor tissue and peripheral blood was extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(65 reference statements)
0
0
0
Order By: Relevance
“…It is noteworthy that our cohort is the first to identify this rare condition. Recent studies have identified unique mutations in the ANO5 gene in FGC, not seen in other BFOLs ( Zhou et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that our cohort is the first to identify this rare condition. Recent studies have identified unique mutations in the ANO5 gene in FGC, not seen in other BFOLs ( Zhou et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%